Utility of Stimulated Thyroglobulin in Reclassifying Low Risk Thyroid Cancer Patients’ Following Thyroidectomy and Radioactive Iodine Ablation: A 7-Year Prospective Trial - Jammah, Anwar A.; Masood, Afshan; Akkielah, Layan A.; Alhaddad, Shaimaa; Alhaddad, Maath A.; Alharbi, Mariam; Alguwaihes, Abdullah; Alzahrani, Saad (Frontiers in Endocrinology, 2021)
Context: Following total thyroidectomy and radioactive iodine (RAI) ablation, serum thyroglobulin levels should be undetectable to assure that patients are excellent responders and at very low risk of recurrence. Objective: To assess the utility of stimulated (sTg) and non-stimulated (nsTg) thyroglobulin levels in prediction of patients outcomes with differentiated thyroid cancer (DTC) following total thyroidectomy and RAI ablation. Method: A prospective observational study conducted at University Hospital in Saudi Arabia. Patients diagnosed with differentiated thyroid cancer and were post total thyroidectomy and RAI ablation. Thyroglobulin levels (nsTg and sTg) were estimated 3-6 months post-RAI. Patients with nsTg <2 ng/mL were stratified based their levels and they were followed-up for 5 years and clinical responses were measured. Results: Of 196 patients, nsTg levels were <0.1 ng/mL in 122 (62%) patients and 0.1-2.0 ng/mL in 74 (38%). Of 122 patients with nsTg <0.1 ng/mL, 120 (98%) had sTg levels <1 ng/mL, with no structural or functional disease. sTg levels >1 occurred in 26 (35%) of patients with nsTg 0.1-2.0 ng/mL, 11 (15%) had structural incomplete response. None of the patients with sTg levels <1 ng/mL developed structural or functional disease over the follow-up period. Conclusion: Suppressed thyroglobulin (nsTg) level <0.1 ng/mL indicates a very low risk of recurrence that does not require stimulation. Stimulated thyroglobulin is beneficial with nsTg 0.1- 2 ng/mL for re-classifying patients and estimating their risk for incomplete responses over a 7 years follow-up period.